MENGELOLA SAMPAH MENJADI OBJEK WISATA YANG ASRI, BERSIH DAN SEHAT DI DESA JATILUWIH TABANAN - BALI - Kadek Januarsa Adi Sudharma; I Kadek Widi Pranajaya (Politeknik Negeri Sriwijaya, 2023)
Jatiluwih Village is a village located in Tabanan Regency where this village is famous for its unique natural charm. The village government certainly tries to deal with every waste problem that occurs in the Jatiluwih Village area. Efforts made by the government to overcome the waste problems that occur are with the TPS3R (Waste Processing Site with the 3R Concept). TPS3R is a waste processing site with the 3R concept (Reduce, Reuse, Recycle) where its application can further help reduce the high volume of waste that accumulates both in the surrounding environment and TPA (Final Disposal Sites) and this concept is more environmentally friendly. Even though Jatiluwih Village already has a TPS3R, the local community still does not understand the function of the TPS3R and the waste segregation process. Therefore the author provides a solution by carrying out a work program for making educational videos about waste sorting at TPS3R Jatiluwih Village. This research method is a qualitative method to find out information related to waste sorting at TPS3R Jatiluwih Village. The research technique applied is by way of field surveys and interviews